The Birth of Batak Toba Community in Kotapinang - Agata Murroisa P.; Daulat Saragi; Phil Ichwan Azhari (Britain International for Academic Research (BIAR) Publisher, 2020)
Toba Batak people believe that there is a rite that will be passed by all humans, namely: Birth, Marriage and death. When the process of birth, marriage and death take place then there is a belief that every time they pass through these rites, humans must hold a tradition that aims as gratitude for the achievement and to avoid disaster. The author takes the focus in the birth rite, because in this birth rite there is a belief in the Toba Batak community of supernatural powers that can interfere at any time than mothers and newborns. The Toba Batak people believe that every new mother and baby undergo surgery, both normally and through surgery in vulnerable and weak conditions so that efforts are needed to keep mothers and newborns away from the evil spirit's power. The Toba Batak community had long ago made various efforts aimed at keeping mothers and babies away from these evil forces, namely by making strings of leaves that had magical powers placed near the mother and newborn, installing fireplaces under the mattress in order to keep the evil forces unable to approach, because according to their beliefs, the evil forces did not dare to heat. From all these efforts, it turns out that the medical benefits of all these efforts can be explained, one of which is by placing a string of cereals, cereals can ward off mosquitoes, while the embers installed under the bed to keep mothers and newborns warm at night days and can recover immediately from the former operation of the birth process. All of these efforts have the aim of avoiding accidents, and this tradition has a path from the beginning of birth until seven days after birth, when arriving on the seventh day a thanksgiving event is known as Esek-esek. The author sees that there are many advantages to this tradition. Aside from keeping mothers and babies away from magical power, it can also be a place for community to gather, so that they can become a place of friendship between the far and near.